Discovery of the new class I methanol maser transition at 23.4 GHz - Voronkov, M.; Walsh, Andrew; Caswell, J.; Ellingsen, S.; Breen, S.; Longmore, S.; Purcell, C.; Urquhart, J. (Oxford University Press, 2011)
We report the first detection of a methanol maser in the 101–92 A- transition at 23.4 GHz,discovered during the H2O southern Galactic Plane Survey (HOPS) with the 22-m MopraRadio Telescope. In the region covered by HOPS, the 23.4-GHz maser was found at onlyone location, G357.97-0.16, which was also a prominent source of maser emission in theJ2–J1 E series near 25 GHz. The Australia Telescope Compact Array (ATCA) was used tofollowup these detections at high angular resolution and prove the maser nature of the observedemission. The analysis shows that the new methanol maser at 23.4 GHz is a class I maser,which has properties similar to the 9.9- and 25-GHz masers (i.e. traces strong shocks withhigher than average temperature and density). All class I masers were found to originate at thesame spatial location (within the measurement uncertainty of 0.5 arcsec) in the vicinity of thedominant infrared source, but at a clearly distinct position from nearby OH, H2O and class IImethanol masers at 6.7 GHz. All maser species are distributed approximately on a line, butit is not clear at present whether this has any physical significance. We also detected a weak(1.3 mJy) continuum source at 25 GHz near the OH maser (at the most northern site, associatedwith a class II methanol maser and an H2O maser renowned for its extremely wide spread ofvelocity components). The continuum source has not been reported at lower frequencies andis therefore a candidate hypercompact HII region.We also used the ATCA to find the strongestand only the fifth known 9.9-GHz maser towards G357.97-0.16 and another 23.4-GHz masertowards G343.12-0.06 not seen in HOPS.